PERAN TEKNOLOGI TELEVISI DALAM MENINGKATKAN KUALITAS PEMBELAJARAN MICROTEACHING - Ahmad Zidan Faris; Rendi Setiyawan; Amliur Rohmah; Diya Nur Ramadani; Syifa Fatimatuzahro; Rina Safira (SPESIFIK: Jurnal Pendidikan dan Pembelajaran, 2026)
Quality education cannot be separated from the optimization of educational facilities and infrastructure as essential supports in the learning process, including in microteaching practices at the university level. This article aims to analyze the role and optimization of television (TV) as an instructional medium in microteaching activities. Through a literature review approach, this study identifies that TV functions not only as a visual aid for presenting instructional materials, learning videos, and teaching simulations, but also as a reflective and evaluative tool for assessing pre-service teachers’ performance. The effective utilization of TV can enhance clarity in content delivery, increase student engagement, and improve the pedagogical competence of university students in designing and implementing instruction. However, several challenges remain, including limited facilities, insufficient technological proficiency, and the lack of optimal media integration in lesson planning. Therefore, appropriate management strategies, the enhancement of technological competencies among students and lecturers, and institutional support in providing adequate facilities are required to maximize the benefits of TV in microteaching practices.